1988
DOI: 10.1039/dt9880000363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and spectroscopic and magnetic properties of catena-µ-aqua-diaquabis(2,6-dimethoxybenzoato)metal(II) monohydrate complexes of manganese, cobalt, nickel, and zinc. X-Ray crystal structure of [Co(dmba)2(H2O)3]·H2O

Abstract: ChemInform Abstract The title complexes (I) are prepared by reaction of stoichiometric amounts of the metal sulfate or acetate with the ligand in hot aqueous solution at pH 4-5 (no yields given). The Co complex (Ia) is investigated by X-ray diffraction (Pna21, Z=4), the compound is polymeric, the metal ion is six-coordinate, the equatorial ligands being mutually trans water molecules and two unidentate carboxylate groups, the metals are linked to each other by bridging water molecules to form an infinite chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…at 5 K. The behaviour indicates strong intramolecular antiferromagnetic coupling of the high-spin cobalt irons, tending to a diamagnetic (S = 0) ground state. In this case, the molar paramagnetic susceptibility data are fit an expression[29], which is based on the general isotropic exchange Hamiltonian, bH ¼ À2J b S 1 Á b S 2 , with J =magnetic exchange coupling constant and S 1 = S 2 = 3/2: v M ¼ 2Ng 2 b 2 kT 14 þ 5 expðÀ6 J=kTÞ þ expðÀ10 J=kTÞ 7 þ 5 expðÀ6 J=kTÞ þ 3 expðÀ10 J=kTÞ þ expðÀ12 J=kTÞ þ N a…”
mentioning
confidence: 99%
“…at 5 K. The behaviour indicates strong intramolecular antiferromagnetic coupling of the high-spin cobalt irons, tending to a diamagnetic (S = 0) ground state. In this case, the molar paramagnetic susceptibility data are fit an expression[29], which is based on the general isotropic exchange Hamiltonian, bH ¼ À2J b S 1 Á b S 2 , with J =magnetic exchange coupling constant and S 1 = S 2 = 3/2: v M ¼ 2Ng 2 b 2 kT 14 þ 5 expðÀ6 J=kTÞ þ expðÀ10 J=kTÞ 7 þ 5 expðÀ6 J=kTÞ þ 3 expðÀ10 J=kTÞ þ expðÀ12 J=kTÞ þ N a…”
mentioning
confidence: 99%
“…using only the carboxylate group, in either a monodentate or bidentate-chelating modes, or through the carboxylate group along with an adjacent hydroxyl in a salicylate-type chelate. Several complexes with d-transition metals [Cu 2+ (Cariati et al, 1983), Co 2+ (Erre et al, 1988), Re 5+ (Bandoli et al, 1999), Pb 2+ (Glowiak et al, 1992) and Mn 2+ (Erre et al, 2000;Glowiak et al, 1995)] and lanthanide ions (Glowiak et al, 1999) have been reported. Several co-crystals of 2,6-Hdhb with other organic ligands have also been reported (Gdaniec et al, 1994;Lynch et al, 1994;Tarnura et al, 1973).…”
Section: Sup-1mentioning
confidence: 99%
“…In continuation of our studies on the development and preparation of 1D, 2D, and 3D coordination polymers5 we herein report the synthesis of three Mn II and Co II complexes, namely [Mn 3 (dmb) 6 (H 2 O) 4 (4, 4′‐bpy) 3 (EtOH)] n ( 1 ), and [ M (dmb) 2 (pyz) 2 (H 2 O) 2 ] [ M II = Co ( 2 ), Mn ( 3 )] with 2, 6‐dimethoxybenzoic acid (Hdmb) and ancillary N‐bridging ligands such as 4, 4′‐bipyridine (4, 4′‐bpy) and pyrazine (pyz). Note that the analysis of structural data (CSD version 5.34) of the metal complexes with the 2, 6‐dimethoxybenzoic acid revealed mononuclear complexes with dioxo‐uranium(VI) ions, [UO 2 (dmb) 2 (H 2 O) 2 ] · H 2 O,6 and dimers with copper(II) ions, [Cu(dmb)(H 2 O)] 2 and [Cu(dmb)(MeCO 2 )(H 2 O)];7 and only water‐bridged 1D polymer structures such as [ M (dmb) 2 (H 2 O) 3 ] · n H 2 O ( M II = Mn, Co, Ni, and Zn)8 were reported. By using additional N‐donor ligands such as 2, 2′:6′,2′′‐terpyridine (terpy), 2‐methylpyrazine (2‐Mepyz), or 1, 3‐bis(2, 6‐diisopropyl)‐phenyl‐imidazol‐2‐ylidene (IPr) the mononuclear Mn II complexes [Mn(dmb) 2 (terpy)]9 and [Mn(dmb) 2 (2‐Mepyz) 2 (H 2 O)],10 and the gold(I) complex [Au(dmb)(IPr)]11 were synthesized, whereas the employment of 2, 2′‐bypyridine (bpy) or 4, 7‐dimethyl‐1, 10‐phenanthroline (Me 2 phen) together with [Mn(dmb) 2 (H 2 O) 3 ] · n H 2 O led to the formation of dimeric compounds, [Mn(dmb)(bpy)(H 2 O)] 2 bpy10 and [Mn(dmb)(Me 2 phen)(H 2 O)] 2 · 2EtOH 12.…”
Section: Introductionmentioning
confidence: 99%